Analisis Tingkat Kesenjangan Bantuan Pangan Non Tunai (BPNT) dan Dampaknya terhadap Daya Beli Masyarakat Muslim - Nur Hana; A Ika Fahrika (Program Studi Akuntansi Syariah, 2022)
Research on Non-Cash Food Assistance (BPNT) from the aspect of equity, it turns out that no one has done it yet. Therefore, this thesis is here to discuss this matter, and herein lies the difference from the results of previous research on BPNT. In researching BPNT from the aspect of equity, a quantitative approach is used for the methodological aspects and Islamic economics for the scientific aspects. To realize these two approaches, an equity model is used in discussing the gap in Non-Cash Food Assistance (BPNT) in Cenrana District, Bone Regency. In proving this, two research questions are proposed, namely: (1) What is the level of inequality in Non-Cash Food Assistance (BPNT) that occurs in Cenrana District, Bone Regency? and (2) What is the impact on the purchasing power of Muslim communities in Cenrana District, Bone Regency. To answer the two research questions, statistical data obtained from each of the seven villages in Cenrana is needed, and also supported by documentation to strengthen the research results. The statistical data were analyzed using a quantitative approach through the Microsoft Excel application, and the results were interpreted using the theory of income distribution and sharia maqasid. The results show: (1) The BPNT gap that occurred in Cenrana District, Bone Regency from 2018-2020 is a moderate (normal) gap, where in 2018 the gap was at the point of 0.45789 then in 2019 the Gini ratio point showed 0.46709 and in 2020 it is at the point of 0.46293 and the Lorenz curve tends to experience an ideal distribution line. (2) The impact on the purchasing power of the Muslim community in Cenrana District, Bone Regency, is a decrease in purchasing power. Due to inequality in the distribution of non-cash food assistance (BPNT).